Identification of Rubisco rbcL and rbcS in Camellia oleifera and their potential as molecular markers for selection of high tea oil cultivars - Chen, Yongzhong; Wang, Baoming; Chen, Jianjun; Wang, Xiangnan; Wang, Rui; Peng, Shaofeng; Chen, Longsheng; Ma, Li; Luo, Jian (Frontiers in Plant Science, 2015)
Tea oil derived from seeds of Camellia oleifera Abel. is a high-quality edible oil in China. This study isolated full-length cDNAs of Rubisco subunits rbcL and rbcS from C. oleifera. The rbcL has 1,522 bp with a 1,425 bp coding region, encoding 475 amino acids; and the rbcS has 841 bp containing a 528 bp coding region, encoding 176 amino acids. The expression level of the two genes, designated as Co-rbcL and Co-rbcS, was determined in three C. oleifera cultivars: Hengchong 8, Xianglin 1, and Xianglin 14 whose annual oil yields were 546.9, 591.4, and 657.7 kg ha-1, respectively. The Co-rbcL expression in ‘Xianglin 14’ was significantly higher than ‘Xianglin 1’, and ‘Xianglin 1’ was greater than ‘Hengchong 89’. The expression levels of Co-rbcS in ‘Xianglin 1’ and ‘Xianglin 14’ were similar but were significantly greater than in ‘Hengchong 89’. The net photosynthetic rate of ‘Xianglin 14’ was significantly higher than ‘Xianglin 1’, and ‘Xianglin 1’ was higher than ‘Hengchong 89’. Pearson’s correlation analysis showed that seed yields and oil yields were highly correlated with the expression level of Co-rbcL at P  0.001 level, and the expression of Co-rbcS was correlated with oil yield at P  0.01 level. Net photosynthetic rate was also correlated with oil yields and seed yields at P  0.001 and P  0.01 levels, respectively. Our results suggest that Co-rbcS and Co-rbcL in particular could potentially be molecular markers for early selection of high oil yield cultivars. In combination with the measurement of net photosynthetic rates, the early identification of potential high oil production cultivars would significantly shorten plant breeding time and increase breeding efficiency.